Endoscopic Resection Followed by Proton Therapy With Pencil Beam Scanning for Skull Base Tumors. (12th September 2018) - Leeman, Jonathan E.; Lee, Nancy Y.; Zhou, Ying; Neal, Brian; Sine, Kevin; Tabar, Viviane; Cohen, Marc A.
Abstract : For patients who require postoperative radiotherapy after endoscopic resection of skull base tumors, proton therapy with pencil beam scanning (PBS) may allow sparing of normal tissue compared to intensity‐modulated photon radiation (IMRT). We compared PBS and IMRT radiation plans in the preoperative and postoperative settings for two patients with advanced skull base tumors following endoscopic resection. The benefits of PBS over IMRT appear greater in the postoperative setting following endoscopic resection with improved sparing of critical organs at risk. The multidisciplinary approach of endoscopic resection followed by PBS represents a treatment paradigm with potential for improvements in toxicity reduction. Laryngoscope, 129:1313–1317, 2019